Respuesta :

Answer:

(15-7)-(8-3)

Step-by-step explanation:

1.

[tex]7+(31-4)(2)\\\\\mathrm{Follow\:the\:PEMDAS\:order\:of\:operations}\\\\\mathrm{Calculate\:within\:parentheses}\:\left(31-4\right)\::\quad 27\\\\=7+27\left(2\right)\\\\\mathrm{Multiply\:and\:divide\:\left(left\:to\:right\right)}\:27\left(2\right)\:\\:\quad 54\\\\=7+54\\\\\mathrm{Add\:and\:subtract\:\left(left\:to\:right\right)}\:7+54\:\\:\quad 61[/tex]

2.

[tex]-212-(-3)\\\\\mathrm{Apply\:rule}\:-\left(-a\right)=a\\\\=-212+3\\\\=-209[/tex]

3.

[tex](15-7)-(8-3)\\\\\mathrm{Follow\:the\:PEMDAS\:order\:of\:operations}\\\\\mathrm{Calculate\:within\:parentheses}\:\left(15-7\right)\::\quad 8\\\\=8-\left(8-3\right)\\\\\mathrm{Calculate\:within\:parentheses}\:\left(8-3\right)\::\quad 5\\\\=8-5\\\\\mathrm{Add\:and\:subtract\:\left(left\:to\:right\right)}\:8-5\:\\:\quad 3[/tex]

4.

[tex]-5[7+(-14)]-30\\\\\mathrm{Follow\:the\:PEMDAS\:order\:of\:operations}\\\\\mathrm{Calculate\:within\:parentheses}\:\left[7+\left(-14\right)\right]\::\quad -7\\\\=-5\left(-7\right)-30\\\\\mathrm{Multiply\:and\:divide\:\left(left\:to\:right\right)}\:-5\left(-7\right)\::\quad 35\\\\=35-30\\\\= 5[/tex]